2020
DOI: 10.3390/molecules25235630
|View full text |Cite
|
Sign up to set email alerts
|

Minerals in Pregnancy and Their Impact on Child Growth and Development

Abstract: During pregnancy, women undergo metabolic and physiological changes, and their needs are higher, to maintain growth and development of the fetus. If the nutritional status of the expectant mother is not satisfactory, some maternal and neonatal complications can occur. In the second and third trimester of pregnancy, there is a reserve of nutrients in the fetus that can be utilized after birth; thereby, children present an accelerated growth in the first years of life, which is a proven response to the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 103 publications
0
45
0
2
Order By: Relevance
“…What is more, the results of some studies [ 16 ] suggest that gestational zinc deficiency may reduce the learning ability, attention and memory in offspring, since the hippocampus has a high zinc concentration. In turn, iron deficiency during pregnancy may lead to severe consequences, including an impaired immune-inflammatory system, premature birth and fetal death [ 17 ]. The results of some studies [ 18 , 19 ] have shown that even exclusively breasted infants may be at risk of zinc and iron deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the results of some studies [ 16 ] suggest that gestational zinc deficiency may reduce the learning ability, attention and memory in offspring, since the hippocampus has a high zinc concentration. In turn, iron deficiency during pregnancy may lead to severe consequences, including an impaired immune-inflammatory system, premature birth and fetal death [ 17 ]. The results of some studies [ 18 , 19 ] have shown that even exclusively breasted infants may be at risk of zinc and iron deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nutrition has been shown to be important for pregnancy and fetal development [ 1 , 2 ]. During pregnancy, the continuous physiological changes in the mother and the development of the fetus are dependent on the supply of specific nutrients [ 1 , 3 , 4 ]. Both nutrient deficiency and oversupply have been associated with adverse pregnancy, fetal, and neonatal outcomes, including preterm delivery, intrauterine growth restriction, and low birth weight, which are the leading causes of neonatal death [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, during preconception and gestation periods, a maternal Se deficient diet can cause complications both in mothers and fetus. Some of these problems may be pre-eclampsia, glucose intolerance, alterations in the lipidic profile, IUGR, mental and psychomotor delay, premature birth or miscarriage [ 60 , 88 , 89 , 90 , 91 ].…”
Section: Low Se and Fetal Programmingmentioning
confidence: 99%
“…For all these reasons, a Se-compromised status particularly affects the lactation period development. As explained before, it is well established that a proper Se amount is necessary during the reproductive period to guarantee an adequate transference of this mineral, via placenta or mammary glands, to pups [ 18 , 88 , 91 , 94 ]. However, during the lactation period, another tissue related to Se absorption is compromised, the gastrointestinal tract (GIT), since this tissue has to adapt itself to the new functions it would lead after birth.…”
Section: Low Se and Fetal Programmingmentioning
confidence: 99%